2008
DOI: 10.1021/jf8015392
|View full text |Cite
|
Sign up to set email alerts
|

Black Soybean Promotes the Formation of Active Components with Antihepatoma Activity in the Fermentation Product of Agaricus blazei

Abstract: The antihepatoma activity and related active components in the fermentation products of Agaricus blazei (AB) cultured in the medium containing soybean (S) or black soybean (BS) were investigated. AB(BS)-pE and AB(S)-pE were the ethanolic extracts from the fermentation products of AB(BS) and AB(S), respectively. According to the IC 50 values, AB(BS)-pE (161.1 and 24.0 microg/mL for Hep 3B and Hep G2 cells, respectively) exhibited stronger cytotoxicities against hepatoma cells than AB(S)-pE (>200 and 99.9 microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…For instance, the β-glucan from A. blazei protected against benzo(á)pyrene induced DNA damage in HepG2 cells by binding to the carcinogen, scavenging free radicals and probably modulating cell metabolism [ 130 ]. Two compounds, namely blazeispirols A and C from A. blazei displayed potent antiproliferative activities against Hep3B cells (IC 50 , 2.8 and 4.5 μg/mL) and HepG2 cells (IC 50 , 1.4 and 2.0 μg/mL) [ 131 ]. Mechanistic study reported that bazeispirol A inhibited Hep3B cancer cell growth in a dose- and time-dependent manner through promoting apoptotic death [ 132 ].…”
Section: Edible Macro-fungimentioning
confidence: 99%
“…For instance, the β-glucan from A. blazei protected against benzo(á)pyrene induced DNA damage in HepG2 cells by binding to the carcinogen, scavenging free radicals and probably modulating cell metabolism [ 130 ]. Two compounds, namely blazeispirols A and C from A. blazei displayed potent antiproliferative activities against Hep3B cells (IC 50 , 2.8 and 4.5 μg/mL) and HepG2 cells (IC 50 , 1.4 and 2.0 μg/mL) [ 131 ]. Mechanistic study reported that bazeispirol A inhibited Hep3B cancer cell growth in a dose- and time-dependent manner through promoting apoptotic death [ 132 ].…”
Section: Edible Macro-fungimentioning
confidence: 99%
“…In our previous study, we also found that BS modified the antihepatoma activity of Agaricus blazei against Hep 3B and Hep G2 cells because it promoted the production of the active compounds. [39] It was reported that β-glucosidase from GL mycelia converted isoflavone glucosides into isoflavone aglycones when soybean extracts were cultivated with GL. [15] Therefore, we speculated that GL might convert the inactive components in BS or AM into active ones during the fermentation process in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, soybean contains fatty acids, squalene, and phytosterol,[40] which could be the starting materials to biosynthesize active compounds such as cytotoxic steroids in A. blazei fermentation products. [4142] In contrast, BS and AM might promote the production of active secondary metabolites in the GL fermentation products. Other components existing in BS or AM could also affect enzymatic activities for the biosynthesis of the major components, including trace elements, phenolic compounds, isoflavones, anthocyanins, saponins, etc.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies on in vivo models might be due to administration of a single component of the fungus, as polysaccharides, or whole fungus, and different methods of administration and concentration of Agaricus extract. For example, the molecules blazeispirols A and C were found in the mycelia but not in the broth of Agaricus cultured in medium containing soybean or black soybean (Su, Hwang, Kuo, Shu, & Sheen, 2008). Also, in another study, it was observed that aqueous extract of Agaricus given in the drinking water to rats and mice exhibited antimutagenic effects but was ineffective when administered in the post-induction period (Barbisan et al, 2002;Barbisan et al, 2003;Delmanto et al, 2001); however, the mushroom given in the dry powdered form to rats at 10% of the diet exhibited significant anti-mutagenic activity (Pinheiro et al, 2003) suggesting that some active constituent was lost during the aqueous extraction.…”
Section: Discussionmentioning
confidence: 99%